Produção de uma xilanase recombinante de Streptomyces sp. S27 e aplicações biotecnológicas - Cunha, Carolina Cândida de Queiroz Brito (2016)
The xylan-degrading enzymes are responsible for the hydrolysis of xylan and can be produced by a variety of microorganisms such as bacteria and fungi. Bacteria produce an effective xylanolytic system composed of endoxylanase, β-xylosidases, arabinofuronosidases, glucuronidases, acetyl xylan esterase and esterase ferulic acid and have been the target of several studies on the production and application of these enzymes in biotechnological processes such as hydrolysis of different substrates to obtain fermentable sugars. Actinomycetes comprising a phylum Gram positive, aerobic, which generally form branched filaments, often in the form of mycelium. Among the actinomycetes, bacteria of the genus Streptomyces in particular, have been studied due to their important role biotechnology. In the present study, we report the expression, purification and characterization of xylanase (XynBS27) recombinantly in yeast P. pastoris. To achieve high levels of production, the gene was designed and synthesized by optimizing codon usage for P. pastoris. The synthetic gene (xynBS27) was cloned into expression vector containing the AOXI promoter followed by integration into the yeast genome. The increased production of XynBS27 was after 96 h of induction, 2% methanol at 28 °C and 200 rpm (80 U/mL), the enzyme was purified in one chromatography step molecular exclusion obtained specific activity of 8525 U/ mg its highest activity at 75 °C and pH 6, it is thermostable and showed stability at pH 5, 6 and 7. The XynBS27 has a molecular mass of 19 kDa active in zymography. Many ions were tested Al3+, NH4+, Ba2+ and Mg2+ were inducers and Ag+ ions, Hg2+ and Cu2+ inhibited, the sulfides of Mn2+, Zn2+, Fe3+ and denaturing agents EDTA and SDS inhibited XynBS27. The enzyme is tolerant to high concentrations of glucose and xylose. The Km and Vmax values were 12.38 mg/mL, 13.679 mmol/(min.mL), respectively, Ki of 180 mM competitive inhibition. The use of the enzyme in baking has proved very promising in the evaluated parameters, volume, density, reducing sugar, stiffness, consistency, firmness and water retention.